Sweep Frequency Response Analysis for Assessment Deformation Core at Power Transformer - Wilarso, Wilarso; Saepudin, Asep; Sholih, Hilman; Dharmanto, Asep (Journal of Engineering and Scientific Research, 2024)
SFRA (Sweep Frequency Response Analysis) is a transportation test where one of the purposes of this test is to ensure that the core of the power transformer does not shift due to the journey from the factory to the field. The SFRA testing is divided into 4 frequency range areas from 20 Hz to 20 MHz and this research is focused on the frequency range below 2 KHz, based on experience at this frequency to check transformer core problems and specific failures in shifting power transformer cores. Based on the comparison results of SFRA testing carried out at the power transformer factory during the FAT (Factory Assessment Test) with testing in the field during the first SAT (Site Assessment Test) and with the second SAT testing, there are differences in the frequency area below 2 KHz, this shows that there is a problem in the area power transformer core, before drawing a final conclusion that there is a problem or deformation in the transformer core, you must look at the results of other tests carried out in the field such as ratio test, winding resistance test, tangent delta test, excitation current test, insulation resistance (megger test). ) winding and core-frame as well as impact recorder data during the journey from the factory to the field. If all other field test results are good then the power transformer is still in good condition and ready to operate and the difference in the graph at a frequency of less than 2 KHz in the SFRA test during SAT compared to when FAT is likely to be caused by residual magnetism that is still on the core side due to testing. DC before or. Residual magnetism can occur due to static electrical phenomena due to the oil purification process or due to the induction effect of the network grounding system where the power transformer is placed